System for reception and risk classification in obstetrics: a technical quality assessment - Rodolfo Cristiano Serafim; Milena Jamas Temer; Cristina Maria Garcia de Lima Parada; Heloisa Helena Ciqueto Peres; Clarita Terra Rodrigues Serafim; Rodrigo Jensen (Universidade de São Paulo, 2020)
Objective: to assess the technical quality of a decision support system for reception and risk classification in obstetrics. Method: a methodological study of assessment of the system. 12 nurses and 11 information technology (IT) professionals were invited to evaluate the Obstetrics Reception and Risk Classification System (Sistema de Acolhimento e Classificação de Risco em Obstetrícia, SACR-O). Based on the standards of the International Organization for Standardization, the minimum number of evaluators and the characteristics to be evaluated were established: functional suitability, reliability, usability, performance efficiency, compatibility, safety, maintainability, and portability. The characteristics assessed should be given a ≥70% positive assessment to be considered suitable. Results: the characteristics assessed by the nurses and the IT professionals, respectively, were considered adequate: Functional suitability (97% and 98%), Reliability (91% and 94%), Usability (89% and 93%), Performance efficiency (97% and 98%), Compatibility (93% and 100%), and System security (95% and 97%). Maintainability (87%) and Portability (97%) were also evaluated by IT professionals. Conclusion: the technical quality of the SACR-O system was considered excellent by nurses and IT professionals.